2019
DOI: 10.1007/s00603-019-01907-4
|View full text |Cite
|
Sign up to set email alerts
|

A Stochastic Study of Flow Anisotropy and Channelling in Open Rough Fractures

Abstract: The quantification of fluid flow in rough fractures is of high interest for reservoir engineering, especially for deep geothermal applications. Herein, rough self-affine fractures are stochastically generated with incremental shear displacement and geometrically described by two aperture definitions, the vertical aperture a vert and the effective aperture a eff. In order to compare their effect on fracture flow, such as anisotropy and channelling, Local Cubic Law (LCL) model-based 2D fluid flow is simulated. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 38 publications
3
13
0
Order By: Relevance
“…The first nucleation point of substantial fracture growth appears to determine the trajectory a propagating fracture may take. This interpretation is in line with the concept of channelized fluid flow and heterogeneous pore fluid pressure fields in rough-walled fractures (Auradou et al, 2006;Marchand et al, 2019).…”
Section: General Observations and Comparison To Other Sitessupporting
confidence: 87%
“…The first nucleation point of substantial fracture growth appears to determine the trajectory a propagating fracture may take. This interpretation is in line with the concept of channelized fluid flow and heterogeneous pore fluid pressure fields in rough-walled fractures (Auradou et al, 2006;Marchand et al, 2019).…”
Section: General Observations and Comparison To Other Sitessupporting
confidence: 87%
“…For flow perpendicular to the shearing, the mean overestimation is around 1%–9%. The significant differences between the NS simulations are the consequence of the extended travel distance between inlet and outlet (of more than 10%), which leads to reduced local pressure gradients and enhances the anisotropy compared to pure LCL investigations (Marchand et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The ratio of the flow between the two extreme cases, where the flow is oriented perpendicular or parallel to the shearing, is called flow anisotropy (FA) (Auradou et al., 2006). Besides laboratory experiments (Gentier et al., 1997; Rasmuson & Neretnieks, 1986), FA was also investigated numerically (Koyama et al., 2006; Mallikamas & Rajaram, 2005; Marchand et al., 2020). Investigations were mostly limited to linear flow conditions, while nonlinear effects were only briefly addressed (Liu et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Koyama et al [1] performed numerical studies on the effect of anisotropy on flow at different scales, which shows during the direct shear test, the aperture was not identical, which causes anisotropy in the flow. Marchand et al [9] demonstrated that flow anisotropy is dependent on changes in fracture aperture. Deng et al [10] showed that anisotropy in hydraulic behavior depends on the anisotropy of the fracture geometry.…”
Section: Introductionmentioning
confidence: 99%